2023
DOI: 10.1371/journal.pgph.0001684
|View full text |Cite
|
Sign up to set email alerts
|

Breaking free from tunnel vision for climate change and health

Abstract: Climate change is widely recognised as the greatest threat to public health this century, but ‘climate change and health’ often refers to a narrow and limited focus on emissions, and the impacts of the climate crisis, rather than a holistic assessment of economic structures and systems of oppression. This tunnel vision misses key aspects of the climate change and health intersection, such as the enforcers of planetary destruction such as the military, police, and trade, and can also lead down dangerous alleywa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Across geographies, this literature signalled a need to consider the historical, political, and geographic contexts of climate change, alongside the structures of power (i.e., Western, colonial, and capitalist worldviews) that constrain climate adaptation and responses and disrupt Indigenous Peoples’ connection to lands and waters. This need to dissect and critically examine the broader context of structural and systemic determinants of climate-health and biodiversity impacts is increasingly the focus of global public health scholarship [ 85 ]. In this light, reviews underscored the need to continue to support, fund, and platform localized, community-led adaptation to climate change and biodiversity loss, while addressing broader sociopolitical constraints to Indigenous Peoples’ community-determination and leadership.…”
Section: Discussionmentioning
confidence: 99%
“…Across geographies, this literature signalled a need to consider the historical, political, and geographic contexts of climate change, alongside the structures of power (i.e., Western, colonial, and capitalist worldviews) that constrain climate adaptation and responses and disrupt Indigenous Peoples’ connection to lands and waters. This need to dissect and critically examine the broader context of structural and systemic determinants of climate-health and biodiversity impacts is increasingly the focus of global public health scholarship [ 85 ]. In this light, reviews underscored the need to continue to support, fund, and platform localized, community-led adaptation to climate change and biodiversity loss, while addressing broader sociopolitical constraints to Indigenous Peoples’ community-determination and leadership.…”
Section: Discussionmentioning
confidence: 99%
“…These emerging research leaders will need a broader range of transferable and leadership skills, including the ability to work across disciplines and sectors [ 37 ]. These are skills that are not traditionally embedded in standard doctoral or postdoctoral training but will be critical to supporting health in this complex and changing environment [ 38 , 39 ]. By investing in the development and support of this rising generation, African nations can harness the power of local expertise to develop sustainable strategies that ensure the well-being of their people in the face of these challenges.…”
Section: Main Textmentioning
confidence: 99%
“…As noted in the table, when AI’s environmental costs are studied, more-than-carbon tunnel vision must be embraced (Deivanayagam & Osborne, 2023 ). Although some authors have concluded that a few AI applications involving telemedicine can reduce the carbon cost of healthcare (Tsagkaris et al, 2021 ), some others remain sceptical about using the carbon footprint as a primary metric (Richie, 2022 ).…”
Section: Short-term Versus Long-term Benefitsmentioning
confidence: 99%